The Effectiveness of the Deductive Method in Increasing the Mastery of Nahwu-Sharaf - Afriati, Intan; Musfina; Nazirah, Jihan; Harira, Dani (DARUSSALAM: Scientific Journal of Islamic Education, 2025)
This article aims to analyze the application of deductive methods in Nahwu and Sharaf learning in Arabic language education. This method emphasizes giving general rules or theories first, followed by examples and application exercises, thus helping students understand complex grammatical concepts systematically and logically. This study uses a literature review approach by examining various relevant reference sources. The results of the study show that the deductive method is effective in facilitating the understanding of the material, especially for complex material, but has a weakness in the form of a class atmosphere that tends to be passive. The conclusion of this article emphasizes that the use of deductive methods must be combined with other media and methods so that learning becomes more interactive and interesting, so that the goals of learning Arabic can be achieved optimally.